Easy-Programming: towards a web collaborating algorithmic and programming aid for early apprentices - Ricardo Vardasca, PhD, ASIS, FRPS (2023)
Science, Technology, Engineering and Mathematics (STEM) under graduate students must develop problem solving skills through algorithmic and programming learning. There are several tools available to aid them in this pro cess but none in a web collaborative environment that can be used for e learning accommodating the three methods available for that development: code, flowchart, and pseudocode. It is aim of this research to outline the exist ing tools and their features, and to propose a new web based collaborative tool accommodating the main features found. An architecture, technological infra structure, database structure, requirements definition, UML use case and class diagrams and a user interface were proposed. New STEM undergraduate stu dents can develop a solid foundation in algorithmic thinking, problem-solving skills, and the ability to effectively communicate and collaborate with others, establishing the foundations for their success in specific fields.